Here are the steps. You give the reasons.
My teacher gave me a home work but I couldn't do it.Pls help me
Question is here:
1)(¬pvq¬)→r/\s (premise)
2)r→t (premise)
3)¬t (premise)
_________________
.'. p (conclusion)
How can we get the conclusion from using the premises (1,2 and 3)?Show that with using rules of inferences.
Here is another proof using contradiction:
1) (~pv~q)------> r^s assumption
2) r---->t.....................assumption
3) ~t...........................assumption
4) ~p..........................assumption for contradiction
5) ~pv~q....................from (4) by using Co...........
6) r^s.........................from (1) and (5) by using M..........
7) r..............................from (6) by using A...........
8) t.............................from (2) and (7) by using M............
9) t ^ ~t from (3) and (8) by using Ad................
But t ^ ~t contradiction hence p